LARANGAN IMPOR PAKAIAN BEKAS BERDASARKAN PERATURAN DI BIDANG PERDAGANGAN TERHADAP PERDAGANGAN PAKAIAN BEKAS DI PASAR SENEN: Prohibition of Used Clothing Imports Based on Regulations of Trade Against Used Clothing Trade in Senen Market - Marlina, Chinta; Abrianti, Sharda (Faculty of Law, Universitas Trisakti, 2024)
Based on the MOT Regulation No. 40 of 2022 on Export-Prohibited Goods and Import- Prohibited Goods, used clothing is one of the goods that are prohibited from being imported. In fact, there are still many imports of used clothing being carried out, evidenced by the existence of a second-hand clothing market in Senen Market. This means that the import of used clothing is still being carried out. The formulation of the problem is how the supervision carried out by the Directorate General of Customs andExcise on the implementation of regulations prohibiting the import of used clothing and how the implementation of the ban on the import of used clothing based on regulations in the field of trade against used clothing trading in Senen Market. The research method uses normative research type, empirical analysis, secondary data supported by interviews, and qualitative analysis. The result is the implementation of the ban on the import of used clothing has not been carried out optimally because there are still many domestic used clothing trades, especially Senen Market. Supervision still has many weaknesses due to the absence of domestic provisions prohibiting the trade in imported used clothing, inadequate human resources and infrastructure in its implementation.